Magic at the Crossroads: Moral Dissonance and Repair in the Wizarding World - Ulugbek Ochilov (Humanities)
The Harry Potter fandom community around the world prefers a universe of wizards and witches that includes all people, but also has concerns about the author’s perspective regarding gender identity. This disjunction paralyzes the cultural reader with moral confusion, which is a danger to their emotional investment in the text. Although scholars have analyzed this phenomenon using fragmented prisms, such as social media activism, cognitive engagement, translation, pedagogy, and fan creativity, there is no unifying model that can be used to understand why reading pleasure endures. This article aims to fill this gap by examining these strands of research in a divergent manner, adopting a convergent mixed-methods study approach. Based on neurocognitive (EEG) values, cross-cultural focus groups, social media analysis, and corpus linguistics, we outline the terrain of reader coping mechanisms. We identify separate fan fractions and examine the corresponding practices. The results are summarized by proposing a model called the MDRL (Moral dissonance repair loop) which is a theoretical model that shows how translation smoothing, pedagogical reframing and fan-based re-moralization interact with one another in creating a system that enables the reader to be collectively able to obtain their relations with the text back to a manageable point and continue being engaged. This model makes a theoretical contribution to new areas in the study of fans, moral psychology, and cognitive literature.